Alteration Of Risk In Asian Bond Markets During And After Mortgage Crisis: Evidence From Value At Risk (Var) Analysis - Günay, Samet (Asian Academy of Management (AAM), 2016)
The bond market is an important source of corporate and national finance. In this study, we analyse the risk level of 10-year government bond yields of four leading Asian countries (South Korea, Japan, Malaysia and Singapore) for two different time intervals: during the period of the mortgage crisis, and the recovery. Risk measurement is conducted via Value at Risk (VaR) analysis, with models (GARCH (1.1) and FIGARCH (1.d.1)) in order to consider changes in variance over time. We also examine the credibility of VaR analysis via the Kupiec LR and DQ tests. According to the results, the highest risk level is seen in the Japan bond market for both periods. Another considerable implication is the significantly rising risk of the Japan bond market, even after the transition from crisis to recovery period. In addition, it is shown that the risk in the Malaysia bond market decreases during the recovery period. However, Kupiec LR and DQ backtesting results demonstrate that this finding is unverifiable.